Ferroptosis in sepsis induced acute lung injury/acute respiratory distress syndrome (ALI/ARDS): a potential therapeutic strategy - Wang, Linlin; Zhang, Wenzhe; Feng, Xiujing (Frontiers in Immunology, 2025)
Sepsis induced acute lung injury/acute respiratory distress syndrome (ALI/ARDS) remains a devastating complication of sepsis, marked by uncontrolled pulmonary inflammation, alveolar–capillary barrier disruption, and high mortality. Despite advances in supportive care, no targeted medicines are currently available. Ferroptosis is an iron-dependent and non-apoptotic form of cell death characterized by the iron induced accumulation of lipid reactive oxygen species (ROS). Emerging evidence indicates that ferroptosis is involved in the progression of sepsis induced ALI/ARDS, although the mechanism of action of ferroptosis in sepsis induced ALI/ARDS is still poorly understood. This mini-review summarizes the mechanism of ferroptosis action on sepsis induced ALI/ARDS, with particular focus on immune dysregulation, endothelial/epithelial dysfunction, and oxidative stress. We highlight key molecular pathways, including glutathione peroxidase 4 (GPX4) inactivation, iron metabolism disruption, and lipid peroxidation cascades, supported by both preclinical studies and emerging clinical correlates. Furthermore, discuss the potential therapeutic approaches currently used to treat ARDS. This review also discusses major challenges to clinical translation and highlights further directions for the treatment and prevention of sepsis induced ALI/ARDS.